Structural resistance – competence in social element on digitalisation process of historical archiving - Albert Marvindo; Muhamad Isnaini (Faculty of Communications Science, Dr. Soetomo University, 2024)
Digitisation of archives is an effort to preserve and utilise technology in the field of historical archiving. Archives hold significant value as they serve as authentic evidence and a form of ‘retrieval’ communication between the past, present, and future. The development and implementation of technology, particularly in archiving, are not always fully accepted by the agents who are part of the structure executing the archive digitisation policy. One of the challenges is technological resistance within the social elements of the structure, where the lack of training to improve staff competence is identified as an obstacle in the implementation of the archive digitisation policy. The Adaptive Structuration Theory was used as an analytical lens because it provides a holistic framework on how competence, as a social element, contributes to the success of the archive digitisation policy. The research used a qualitative descriptive method, with a case study approach allowing for more comprehensive research. The research paradigm used was constructivist, viewing knowledge as a social construct emerging from interactions and communication within a sociocultural context.